Genome-wide characterization of the SHORT INTER-NODES/STYLISH and Shi-Related Sequence family in Gossypium hirsutum and functional identification of GhSRS21 under salt stress - Sun, Chendong; Yu, Li; Zhang, Shuojun; Gu, Qijuan; Wang, Mei (Frontiers in Plant Science, 2023)
Saline stress is a significant factor that caused crop growth inhibition and yield decline. SHORT INTERNODES/STYLISH (SHI/STY) and SHI-RELATED SEQUENCE (SRS) transcription factors are specific to plants and share a conserved RING-like zinc-finger domain (CX2CX7CX4CX2C2X6C). However, the functions of SHI/STY and SRS genes in cotton responses to salt stress remain unclear. In this study, 26 GhSRSs were identified in Gossypium hirsutum, which further divided into three subgroups. Phylogenetic analysis of 88 SRSs from8 plant species revealed independent evolutionary pattern in some of SRSs derived from monocots. Conserved domain and subcellular location predication of GhSRSs suggested all of them only contained the conserved RING-like zinc-finger domain (DUF702) domain and belonged to nucleus-localized transcription factors except for the GhSRS22. Furthermore, synteny analysis showed structural variation on chromosomes during the process of cotton polyploidization. Subsequently, expression patterns of GhSRS family members in response to salt and drought stress were analyzed in G. hirsutum and identified a salt stress-inducible gene GhSRS21. The GhSRS21 was proved to localize in the nuclear and silencing it in G. hirsutum increased the cotton resistance to salt using the virus-induced gene silencing (VIGS) system. Finally, our transcriptomic data revealed that GhSRS21 negatively controlled cotton salt tolerance by regulating the balance between ROS production and scavenging. These results will increase our understanding of the SRS gene family in cotton and provide the candidate resistant gene for cotton breeding.